Aplication of Image Processing to Determine The Freshness of Tilapia Fish (Oreochromis niloticus) - Ayu Kalista; Amin Redjo; Umi Rosidah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
The quality of fresh fish will decrease immediately after death. One of the indicators of fish quality is the changes of the gills color. The aim of this research was to determine the changes of red color in the gills of tilapia using image processing as an indicator of fish freshness. The research method used is the Explanatory Research where the independent variable (x) is tilapia which stored at room temperature for 12 hours. The dependent variable (y) was the intensity value of red. The quality of fish could be grouped into several categories, such as high quality, good quality, limit of acceptability and spoilt. The Observation was carried out with a time of 0 hours to 12 hours (4 hour interval). The results showed that storage time affected the deterioration of fresh quality. The high quality category has a red percentage value of 82.18%. Fresh category has a red percentage value of 67.10%. The limit of acceptability category has a value of 38.52% and the spoiltcategory has a red percentage value of 9.92%.